ANALISIS PELAKSANAAN KEBIJAKAN PUBLIK DIBIDANG PELAYANAN KESEHATAN MELALUI BPJS DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 22009 TNTANG PELAYANAN PUBLIK JUNCTO UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Teguh Santoso; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
BPJS Kesehatan Pekanbaru branch is a body formed to carry out public policy namely the National Health Insurance program (JKN) in the city of Pekanbaru. But in the field implementation there are still a number of problems in the implementation of public policies for public health insurance programs, especially in the implementation of health services. The purpose of this thesis writing, namely: First, the implementation of public policy in the field of health services through BPJS Health in the city of Pekanbaru, Second, Constraints faced in the implementation of public policy in the field of health services through BPJS Health in the city of Pekanbaru, Third, the efforts made by BPJS Health to overcome hambata -hambata in the implementation of public policy in the field of health services through BPJS Health in the City of Pekanbaru. This type of research can be classified in the type of sociological research, because in the study the author directly conducts research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru branch of BPJS Health office and also in several health facilities that became partners of the Pekanbaru BPJS Health branch, while the Population and Samples were all parties related to the problems examined in this study, data sources used, primary data, data secondary, and tesier data, data collection techniques in this study with observation, interviews, and questionnaires and literature study. From the results of the research problem there are three main things that can be concluded. First, in the implementation of public policy in the field of health services through BPJS Health is still not satisfactory. Second, the constraints faced are in the scope of BPJS health, in the implementation of health services, and in the community sector; third, the efforts made are by the cooperation of stakeholders related to the implementation of public policy in the field of health services through BPJS Health in the city of Pekanbaru. The author's suggestion, first, so that the Pekanbaru BPJS branch can implement the SOP properly in accordance with the prevailing laws and regulations, secondly, to further enhance the active role of the community and also intensify the socialization; thirdly, invite the parties to be more proactive in implementation of public policy in the field of health services through BPJS Kesehatan in the city of Pekanbaru. Keywords: Implementation – Public Policy - BPJS Kesehatan - Pekanbaru City